Role of lactate level in predicting admission need to intensive care unit and short term outcomes in patients with acute gastrointestinal bleeding - Hekmat Nashat Shawky; Hala Mostafa Kamel; Zain Elabdeen Ahmed Sayed; Hossam Mahmoud Abdelwahab (SpringerOpen, 2024)
Abstract Background One of the most common emergencies seen in emergency departments is acute gastrointestinal bleeding (GIB). It's associated with more disease burden and mortality. Increased venous lactate levels are common in critically ill patients, and it has been used as a possible predictor of patients' outcomes in many critical cases, but not much is known about its predictive role in patients with acute GIB. With increasingly limited health care resources, there has been such an interest in coast saving measures and measuring lactic acid through venous blood gases is such a simple bedside test which can be easily done to patients with acute GIB at emergency department. Objective This study assessed the predictable value of lactate level on hospital admission on resource use, including length of hospital stay and admission to the intensive care unit (ICU), as well as other patient-oriented outcomes, including the need for blood transfusions and endoscopy. Patients and methods A prospective cohort hospital based study that included 300 patients with acute GIB who presented to emergency department (ED) of Assiut University Hospital between September 2019 and June 2022 were subjected to venous blood lactate through venous blood gases. Results The current study enrolled 300 patients with acute GIB. Two hundred of those patients had elevated blood lactate and 100 patients had normal blood lactate. It was found that patients with elevated blood lactate had significantly prolonged hospital stay (7.38 days ± 2.05 days vs. 3.96 days ± 1.74 days; (P < 0.001). Also they had higher frequency of blood transfusion (98% vs. 72%), ICU admission (95% vs. 67%) and mortality (9% vs. 3%) in comparison to those with normal lactate level. Conclusion It was found that venous lactate level is an effective predictor for patient's outcomes among patients with acute GIB.